THE YIN-YANG CONCEPT IN SPATIAL OF HOK TEK BIO CHINESE TEMPLE, PURWOKERTO - Wita Widyandini; Yohana Nursruwening (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2019)
Hok Tek Bio temple is located in the Old Navan Kauman Muslim students. This temple in addition to functioning as a place of worship, also serves as a cultural center of the Chinese community, and socialcenter of the Chinese community in Purwokerto. One of the concepts used in Chinese society in building abuilding is the concept of Yin-Yang, which harmonize between the two conflicting elements that Yin and Yanginto a single unit that is in harmony, and balance. The purpose of this study is to explore and discover the application of the concept of Yin-Yang onspatial in Hok Tek Bio Temple Purwokerto. The method used is qualitative research methods. As for themethod of analysis using descriptive methods. The results of this study are Hok Tek Bio Temple Navan apply the concept of Yin-Yang on spatial. Theapplication of the concept of Yin-Yang is seen in circulation and layout inside the temple. Circulationpatterns in the temple produce imaginary North-South axis that produce spatial patterns in temples thatsymmetry and balance. Keywords:  Yin-Yang, spatial, chinese temple, Hok Tek BioABSTRAK Kelenteng Hok Tek Bio terletak di kawasan muslim santri Kauman Lama Purwokerto.  Kelenteng iniselain berfungsi sebagai tempat ibadah, juga berfungsi sebagai pusat kebudayaan masyarakat Tionghoa, danpusat bersosialisasi masyarakat Tionghoa di Kota Purwokerto. Salah satu konsep yang digunakan masyarakatTionghoa dalam membangun suatu bangunan adalah konsep Yin-Yang, yang menyelaraskan antara duaunsur yang bertentangan yaitu Yin dan Yang menjadi satu kesatuan yang selaras, serasi, dan seimbang.  Tujuan dari penelitian ini adalah menggali dan menemukan penerapan konsep Yin-Yang pada tataruang dalam Kelenteng Hok Tek Bio Purwokerto. Metode penelitian yang digunakan adalah metodepenelitian kualitatif. Adapun untuk metode analisisnya menggunakan metode deskriptif.  Hasil dari penelitian ini adalah Kelenteng Hok Tek Bio Purwokerto menerapkan konsep Yin-Yangpada tata ruangnya. Penerapan konsep Yin-Yang ini terlihat pada sirkulasi dan tata ruang bagian dalamkelenteng. Pola sirkulasi di dalam kelenteng menghasilkan sumbu imajiner Selatan-Utara yang menghasilkanpola tata ruang dalam kelenteng yang simetri dan seimbang.Kata-kata Kunci :  Yin-Yang, tata ruang, kelenteng, Hok Tek Bio